IDENTIFIKASI DAERAH JELAJAH BERUK (Macaca nemestrina Linnaeus, 1766) MENGGUNAKAN APLIKASI SISTEM INFORMASI GEOGRAFIS DI KAWASAN HUTAN UNIVERSITAS RIAU - Eka Surya Ahmadi; Yossi Oktorini; Defri Yoza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Macaca nemestrina is one including appendix II containing list of endangered species. The research aims to understand home range to know daily behavior and mapping range of Macaca nemestrina in the area of Riau University forest and surrounding areas. This research using a method of direct observation by way of follow, noticed as well as record every activity performed by groups of Macaca nemestrina. The determination of the regional daily range in overlay using software arcgis 10.1. Daily activity were analysed by counting average time daily activity and percentage number of daily activity fauna. Home range Macaca nemestrina were analysed using kernel density estimation (KDE) located on program Geospatial Modelling Environment (GME) and ArcGis 10.1. Home range outermost Macaca nemestrina were analysed by the method of Minimum Convex Polygon (MCP). The result showed that Macaca nemestrina in the area of Riau University forest having broad areas of 176.553 m². Maps of the home range Macaca nemestrina having range regions core level very high density area of 7.916 m², high area of 11.344 m², mid 41.468 m², low area of 83.28 m² and level of density is very 32.542 m². The activity of Macaca nemestrina is eat, break, migrates, grooming and social interaction. The highest activity is break activity 36,68%, the lowest activity is grooming 4,10%. The percentage of eating 25,33%, social interaction 29,69% and devolve activity 4,20%. To scatter cruiser regions Macaca nemestrina in forest area of Riau University were on the point coordinates 101°22'44,565'BT–101°23'8,918'BT and 0°28'56,122'LU–0°28' 32,798'LU.Keywords: Macaca nemestrina L., Forest Areas, Daily Range, Home Range, Core Areas, Coordinate.